Adoption of Remote Work in the Nigerian Public Sector: Challenges and Opportunities in Delta State - Okolie, Ugo Chuks; Egbon, Thomastina Nkechi (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study investigates the adoption of remote work in Nigerian public agencies, focusing on the challenges and opportunities associated with teleworking in a sector traditionally centered on office-based operations. The study aims to provide insights into how remote work can be effectively implemented to enhance productivity, employee satisfaction, and organizational flexibility. Methodology: A qualitative research approach was adopted, involving semi-structured interviews with HR managers, policymakers, and employees across various public agencies. Thematic analysis was employed to identify recurring patterns, perceptions, and organizational experiences related to remote work adoption. Results and Findings: The study reveals that while remote work offers opportunities such as increased flexibility, improved work-life balance, and potential cost savings, several challenges hinder its adoption. Key barriers include inadequate ICT infrastructure, lack of formal remote work policies, and low digital literacy among employees. Organizational culture and supervisory practices were found to significantly influence employees’ willingness and ability to engage in telework. Originality: This study contributes to the limited empirical literature on remote work in the Nigerian public sector, highlighting contextual factors unique to government agencies and offering practical insights for HRM practitioners. Conclusion: Strategically planned remote work policies, supported by technological investments and capacity-building initiatives, are essential to successfully integrate teleworking in Nigerian public sector. Type of Paper: Research Article